Peran Dinas Tenaga Kerja Dan Transmigrasi Provinsi DIY Dalam Upaya Mengurangi Angka Pengangguran Pada Era Tatanan Baru di Kota Yogyakarta - Herman Wahyu Dwi Maelana; Khoiri Najib; Himawan Agung Nugroho (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2022)
During the COVID-19 pandemic, the unemployment rate increased because companies reduced the number of employees. The Labor and Transmigration Office of the DIY Province takes a role in reducing unemployment rate in Kota Yogyakarta. The purpose of this study is to explain the role of the Labor and Transmigration Office of DIY Province in an effort to reduce unemployment in the era of the new normal in the city of Yogyakarta. The research data was collected through observation, interviews, document studies and literature studies. The role of the Labor and Transmigration Office of DIY Province, as a result of this research, is to create programs and activities for the community of Kota Yogyakarta so that the community has certified knowledge and abilities, namely the Workforce Certification Activity Program, Apprenticeship Program, Business Assistance Program for Educated Independent Workers ( TKMT) and Technical Guidance for Accreditation and Instructor Accreditation of Job Training Institutes (LPK) and Job Training Centers (BLK).